THE ROLE OF THE GANGGANGPANJANG VILLAGE GOVERNMENT IN THE DEVELOPMENT OF PUNDEN RECO TOURISM - Vera Ferdyana; Eny Rustianingsih (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study aims to analyze the role of the Ganggangpanjang Village Government as a facilitator, mobilizer, and regulator in the development of Punden Mbah Reco tourism. The focus of the study is directed at how these three roles are implemented in an integrated manner to support the balance between economic management, cultural preservation, and environmental sustainability. Method: This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct field observations, and documentation studies. Research informants include the village head, the Tourism Office, the Village Community Empowerment Office, local MSMEs, and tourists. Data analysis was carried out thematically to identify the implementation of each role of the village government. Results: The results of the study show that as a facilitator, the village government provides supporting infrastructure such as road repairs, toilets, prayer rooms, gazebos, and vendor stalls, accompanied by village fund support and long-term planning in the form of tourist maps and historical information boards. As a mobilizer, the village government has succeeded in mobilizing the active participation of the community, especially youth, in daily operations, maintaining cleanliness, and developing MSMEs that support tourism. Meanwhile, as a regulator, the government establishes operational regulations, vendor zoning, and prohibits behavior that violates norms to maintain the cultural value and sacredness of the site. The synergy of these three roles creates participatory, adaptive, and sustainable tourism governance. Novelty: The novelty of this research lies in the integrated mapping of the three roles of village government (facilitator, mobilizer, regulator) as a model for community-based tourism management that can be replicated in other tourism villages. This approach not only strengthens tourist attractions but also ensures cultural and environmental sustainability simultaneously.